PERAN MODAL SOSIAL DALAM PENANGGULANGAN KEMISKINAN MASYARAKAT MISKIN PERKOTAAN PADA PEDAGANG SEKTOR INFORMAL DI KOTA SEMARANG - Munandar, Moh. Arif (Faculty of Social Science, Universitas Negeri Semarang, 2010)
The informal sector trader has a greater chance when they had empowered compared with otherprofessions in vertical mobility among people on low incomes. In addition, based on BPS data from 1996-2008, the condition of the poor in Indonesia has always fl uctuated with the range between 1% to 5%, to riseor fall on the poverty line. This condition indicated that there have not formulated of the poverty reductionyet. This study was to determine the extent of social capitalÃ¢â‚¬â„¢s role in the response to the urban poor in thecommunity of informal sector traders in the city of Semarang on the basis of the pockets of the informalsector as traders in Semarang Jalan Gajah Mada, Pasar Kobong , and bird markets Citarum. Respondentsof this study include the informal sector traders who can represent the data analysis, and respondentswho can provide additional information relating to informal trading sector. Data analysis using qda weftof this study are 1) Categorization of cooperation undertaken in the informal sector traders communityof the urban poor can be divided into joint categorization of low, medium and fairly. Categorization ofthis cooperation is based on how far they can foster capital that can be used as working capital from highlevel. Interactions are very rare which is often done while the low cooperation, 2) Traders prefer informalsector in the form of informal cooperation, 3) Found allegations reason not to develop cooperatives in theinformal sector traders community. 4) In this research can be made categorization Ã¢â‚¬Å“please helpÃ¢â‚¬Â in themerchant community informal.5) community cohesiveness informal traders can be categorized as highsector. This condition is shown from the notion of my (community members) and you (not a member).Key words : Role, urban poor community, traders, informal sector